Study of statistically controlled surface roughness solution in machining of titanium alloys using ultrasonic machining. (13th September 2010) - Singh, Rupinder
The purpose of the present investigations is to study the statistically controlled surface roughness (SR) solution in machining of titanium alloys with ultrasonic machining (USM). In this study, previously developed Taguchi model of SR for USM of titanium and its alloys has been investigated. Relationships between SR and other controllable machining parameters (power rating, tool type, slurry concentration, slurry type, slurry temperature and slurry size) have been deduced. Taguchi design result suggests that slurry temperature significantly affects SR. Strong possibilities are observed for the process under statistical control as regards to SR is concerned at the best settings of input parameters while machining of titanium alloys with USM.